Proceedings of the 10th Annual International Conference on Mobile Computing and Networking 2004
DOI: 10.1145/1023720.1023728
|View full text |Cite
|
Sign up to set email alerts
|

Practical robust localization over large-scale 802.11 wireless networks

Abstract: We demonstrate a system built using probabilistic techniques that allows for remarkably accurate localization across our entire office building using nothing more than the built-in signal intensity meter supplied by standard 802.11 cards. While prior systems have required significant investments of human labor to build a detailed signal map, we can train our system by spending less than one minute per office or region, walking around with a laptop and recording the observed signal intensities of our building's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
443
1
16

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 553 publications
(470 citation statements)
references
References 50 publications
10
443
1
16
Order By: Relevance
“…Therefore, none of the occurrence-based Wi-Fi fingerprints are good at distinguishing rooms. Our results also confirmed the observation (Haeberlen et al 2004 poral variations, we do see good concentration of same-room curves, especially when ordered k-combination is used. Figure 7f-h shows the CDF curves of RSS-Diff for different time periods, using 1-AP, 2-APs, and ordered 2-APs as fingerprints.…”
Section: Temporal Variationsupporting
confidence: 90%
“…Therefore, none of the occurrence-based Wi-Fi fingerprints are good at distinguishing rooms. Our results also confirmed the observation (Haeberlen et al 2004 poral variations, we do see good concentration of same-room curves, especially when ordered k-combination is used. Figure 7f-h shows the CDF curves of RSS-Diff for different time periods, using 1-AP, 2-APs, and ordered 2-APs as fingerprints.…”
Section: Temporal Variationsupporting
confidence: 90%
“…This was the first fingerprinting system that showed that it is possible to localize a laptop in the hallways of a small office building within 2-3 m of its true location, using fingerprints from four 802.11 access points. There have been improvements to Radar's fingerprint matching algorithm that have improved accuracy [2,13,19] and were able to differentiate between floors of a building with a high degree of precision [8]. In addition, commercial localization products have been built using 802.11 fingerprinting [20].…”
Section: Indoor Localization Using 80211 Fingerprintingmentioning
confidence: 99%
“…The initial problems identified with Wi-Fi network localization are that it is not very accurate (up to 1-2 meters accuracy at best) and requires an understanding of the physical layout of the wireless environment. The problem of improving accuracy from RSSI values has been worked on by [9][10][11][12] and a number of algorithms have been proposed with varying results. The problem of the wireless physical environment is one that has been 'passed-off' by a number of commercial applications which put the burden of calibration on network administrators.…”
Section: Location Based Security and Servicesmentioning
confidence: 99%